Need for Parental Control and Mediation in Food Advertising to Children: A Review of Previous Research - Kaur, Pavleen (Information Management and Business Review, 2011)
Food advertising to children is recognised worldwide as contributing to obesity in children. Much of the research in this area has been carried out in US, UK and other developed countries that are fighting the obesity epidemic. The phenomenon is, however, not restricted to the developed world only, but is now trickling down to the developing countries, such as India. Therefore, it is pertinent that necessary measures are devised and implemented so that Indian children may not face the same situation. At present, when governmental regulations are less forthcoming and marketers are enjoying the potential offered by a huge and untapped market for western foods, it becomes imminent for the parents to intervene and protect their children from banal effects of food advertising. Therefore, the present paper seeks to review various studies conducted in this area to highlight the need for TV viewing mediation by parents in the Indian situation.